Microwave assisted hydrothermal method for porous zinc oxide nanostructured-films - Ridha, Noor J; Umar, Akrajas Ali; Alosfur, F; Jumali, Mohammad Hafizuddin Haji; Salleh, Muhamad Mat (Journal of nanoscience and nanotechnology, 2013)
Porous ZnO nanostructures have become the subject of research interest--due to their special structures with high surface to volume ratio that may produce peculiar properties for use in optoelectronics, sensing and catalysis applications. A microwave-assisted hydrothermal method has been used for effecting the formation of porous nanostructure of metaloxide materials, such as CoO and SnO2, in solution. Here, by adopting the unique performance of a microwave-assisted-hydrothermal method, we realized the formation of highly porous ZnO nanostructures directly on the substrate surface, instead of in solution. The effects of the ambient reaction conditions and the microwave power on the structural growth of the ZnO nanostructures were studied in detail. Two different ambient reaction conditions, namely refluxed and isolated in autoclave systems, were used in this work. Porous ZnO (PZO) nanostructures with networked-nanoflakes morphology is the typical result for this approach. It was found that the morphology of the ZnO nanostructures was strongly depended on the ambient conditions of the reaction; the isolated-autoclave system may produce reasonably high porous ZnO that is constituted by vertically oriented grainy-flakes structures, whereas the refluxed system produced solid vertically-oriented flake structures. The microwave power did not influence the structural growth of the ZnO. It was also found that both the ambient reaction conditions and the microwave power used influenced the crystallographic orientation of the PZO. For instance, PZO with dominant (002) Bragg plane could be obtained by using refluxed system, whereas PZO with dominant (101) plane could be realized if using isolated system. For the case of microwave power, the crystallographic orientation of PZO prepared using both systems changed from dominant (002) to (101) planes if the power was increased. The mechanism for the formation of porous ZnO nanostructures using the present approach is proposed. The ZnO nanostructures prepared using the present method should find an extensive use in currently existing application due to its property of reasonably high porosity.